EVIDANCE BASED CASE REPORT (EBCR) : PENGARUH TERAPI MUSIK TERHADAP NYERI PERSALINAN KALA I FASE LATEN DI UPTD PUSKESMAS SUKARASA (Jurnal Kesehatan Siliwangi, 2022)
Background: Labor pain is a physiological condition  that every woman should feel during labor. This pain could  be a source of stress for the mother which has the potential to interfere the labor   progress  as well as  the welfare of the mother and fetus during the delivery. Providing complementary therapies such as music therapy has been proven to  provide relaxing effect for mothers during childbirth thus they can reduce the stress response experienced by mothers. The purpose: of writing EBCR is to determine the effect of music therapy on pain intensity in labor. The method: used in writing EBCR is by searching for evidence through databases from pubmed and Google Scholar with the year of publication 2017-2022. From the search results, 2 articles were found that matched the criteria. Result: Giving music therapy interventions has been proven effective because the mother felt more relaxed and comfortable and reduced pain after music therapy. Conclusion: music therapy can be a non-pharmacological therapy to reduce labor pain.